An econometric investigation of impacts of sustainable land management practices on soil carbon and yield risk: A potential for climate change mitigation - Kato, Edward; Nkonya, Ephraim M.; Place, Frank; Mwanjololo, Majaliwa (International Food Policy Research Institute, 2010)
We investigate the impacts of sustainable land management practices on soil carbon stocks and also impacts of soil carbon on the mean and variance of crop production using econometric tools. Using a cross-sectional plot-level dataset collected from three agroecological zones of Uganda with soil carbon measured at a depth of 0 to 15 centimeters, our results have robustly shown that irrigation, fertilizers, improved fallow, crop residues, mulching, and trash lines are positively and significantly associated with higher soil carbon, corroborating results from agronomic experiments. However, we found crop rotation associated with lower soil carbon, which has also been observed in some agronomic experiments. Soil carbon has shown a significant nonlinear effect on crop production with the threshold occurring at 29.96 milligrams of carbon per hectare, above which farmers start to see significant positive effects on crop production. Furthermore, we found soil carbon to be associated with lower variance of crop production; hence, soil carbon is an indicator of crop yield loss risk (soil carbon has a risk-reducing effect). These empirical results have demonstrated strong evidence for developing countries of the potential of sustainable land management practices to enhance carbon sequestration and also the potential of soil carbon to reduce production risk. The results have implications for the role that soil carbon can play in adaptation to climate change and provision of ecosystem services.